Generating one-dimensional micro- or nano-structures with in-plane alignment by vapor-driven wetting kinetics. Issue 2 (19th January 2017) - Liu, Chuan; Liu, Xuying; Xu, Yong; Sun, Huabin; Li, Yun; Shi, Yi; Lee, Michael V.; Yamada, Toshikazu; Hasegawa, Tatsuo; Noh, Yong-Young; Minari, Takeo
Abstract : The wetting of a droplet on a particular solid surface of a thin liquid film followed by solvent drying is a crucial process for nanostructure formation. Abstract : The wetting of a droplet on a particular solid surface of a thin liquid film followed by solvent drying is a crucial process for nanostructure formation. However, this thin liquid film was commonly observed to rupture due to the instability of the given surface. Herein, we developed a technique to control the dynamical kinetics of a solution droplet by the co-solvent vapor, which yielded a reversible spreading/dewetting process between the spherical droplet and the stable thin liquid layer on surfaces that are usually difficult to wet. Our theoretical model indicates that the wetting process is governed by the sorption of co-solvent vapor within the droplet, which alters the surface free energy, lowers the contact angle, reduces the liquid film thickness, and stabilizes the drying process. The obtained thin liquid films allow the in-plane alignment to generate one-dimensional nano- or micro-structures in the deposited materials, such as nanowires and organic crystals. In particular, in-plane aligned organic single crystals unveiled high field-effect mobility, up to 9.1 cm 2 V −1 s −1, in thin-film transistors.